The BSCBAS: a Balanced Scorecard‐based appraisal system for improving the performance of software organizations. Issue 7 (30th July 2012) - Hamouda, Alaa El‐deen
Abstract Performance appraisals are most commonly undertaken to let an employee know how his/her performance compares to the supervisor's expectations and to identify areas that require training or development. Generally, developing an appraisal system that accurately reflects employee performance is a difficult task. In software companies, such a task is more difficult because software engineering is, by its nature, innovative work. To measure software engineers' performance, the challenge is in having tangible key performance indicators that reflect that performance. In this paper, we present a framework for an appraisal system for software engineers using the Balanced Scorecard methodology. This framework was applied and its influence on the software engineers' performance and the overall performance of the organization was investigated. Copyright © 2012 John Wiley & Sons, Ltd.